Experimental Study of Crack Propagation through Cladded 316L/S355 Steel Produced by the Hot-Roll Bonding Process - Edvard Bjelajac; Andrej Skumavc; Fidan Smaili; Gorazd Lojen; Jožef Predan; Tomaž Vuherer (Metals, 2023)
A hot-rolled clad plate made of 316L stainless steel and S355 carbon steel was produced in a real industrial environment via GMAW welding, vacuuming, preheating to 1240 °C, and hot-roll bonding on four stand plate mills in nine passes with reduction rates between 20-6% per pass. The clad plates were solution annealed to achieve the usual delivery condition. Ultrasound testing showed a bonding rate of 100%. Metallographic examination revealed predominantly low concentrations of oxides at the interface. The tensile strength of the bond reached 155 MPa. The shear strength always satisfied the requirements of ASTM A264. It was observed that the concentration of oxide particles influenced the shear strength strongly. The lowest measured value was 172 MPa. Specimens notched in the base material and specimens notched in the clad layer were used in the Charpy impact test. In every case, only the notched layer broke, while the other layer was only bent. The absorbed energies were always higher than those of each material alone. Fracture mechanic tests gave similar results. The crack could not propagate from the notched layer into the other one, regardless of the material of the notched layer. Instead, delamination occurred. Due to delamination, K1c could not be determined, so KQ was given instead.